Electrolyte Engineering Stabilizes Photoanodes Decorated with Molecular Catalysts. Issue 7 (24th March 2023) - Jenewein, Ken J.; Wang, Yuanxing; Liu, Tianying; McDonald, Tara; Zlatar, Matej; Kulyk, Nadiia; Benavente Llorente, Victoria; Kormányos, Attila; Wang, Dunwei; Cherevko, Serhiy
Abstract: Invited for this month′s cover is the group of Dunwei Wang from Boston College and Serhiy Cherevko from the Helmholtz Institute Erlangen‐Nürnberg for Renewable Energy. The image illustrates the impact of different electrolyte environments on the stability of hematite decorated with an iridium molecular catalyst used for solar water splitting. The Research Article itself is available at 10.1002/cssc.202202319 . Abstract : " The design uses the analogy of having a date night at a bar…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202202319 . View the Front Cover here: 10.1002/cssc.202300405 .